(untitled) (Global Journal of Science Frontier Research, 2018)
Electrochemical behaveour and schme of reduction at electrode of pesticides having different electro active groups to be reduced that is azomethine and double bond carbons at carbon nano tubes paste electrode Using universal buffer as supporting electrolyte and techniques cyclic voltammetry, differential pulse adsorptive stripping voltammetry, milliccoulometry have been studied. All investigatios was made from water samples. The average recoveries obtained for two samples ranged from 97.00% to 99.46%.